The Self-Image of Propaganda: Biopolitics of Yuqing Governance - Wang, Clyde Yicheng (Critical Asian studies, 2024)
This article explores how China's propaganda system operates as an aspect of governance, especially how propagandists understand the public opinion they seek to influence. Understanding the concept of yuqing (public opinion conditions) is crucial for understanding propaganda in China. Yuqing is considered akin to the medical condition of public opinion (yulun). Hence, propaganda is treatment that the state provides to an organic social body of public opinion, which is subject to constant monitoring and treatment. The party-state is keen on establishing standards and norms about what a healthy and clean society should be. Thus, this paper argues that the propaganda system does not contribute to responsive authoritarianism by collecting grassroots information, but instead prioritizes cleansing public discourse in accordance with party-state logic. Furthermore, contrary to the belief that authoritarian propaganda focuses on demobilizing collective resistance and forcing compliance, China's propaganda system disciplines the public by actively constructing discursive norms.